2021
DOI: 10.1159/000517203
|View full text |Cite
|
Sign up to set email alerts
|

Small Choroidal Melanoma: Correlation of Growth Rate with Pathology

Abstract: <b><i>Purpose:</i></b> The aim of the study was to evaluate equivalence of growth rate and pathologic confirmation in small choroidal melanoma (SCM). <b><i>Design:</i></b> This study is a case series. <b><i>Subjects, Participants, and Controls:</i></b> A total of 61 patients with a choroidal melanocytic tumor of size 5.0–16.0 mm in the largest basal diameter and 1.0–2.5 mm in thickness were classified into the pathology-confirmed group (&l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Early detection and treatment of UM is crucial as metastasis events may occur early, and effective treatment can prevent its spread. 45 , 46 Despite the availability of effective treatments for the primary tumor, more than 50% of UM patients develop metastatic disease suggesting that UM may metastasize prior to the time of treatment. 45 , 47 Consequently, there is a need for identifying and treating small UM to minimize the number of melanocytic choroidal tumors that are observed and subsequently grow during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection and treatment of UM is crucial as metastasis events may occur early, and effective treatment can prevent its spread. 45 , 46 Despite the availability of effective treatments for the primary tumor, more than 50% of UM patients develop metastatic disease suggesting that UM may metastasize prior to the time of treatment. 45 , 47 Consequently, there is a need for identifying and treating small UM to minimize the number of melanocytic choroidal tumors that are observed and subsequently grow during the observation period.…”
Section: Discussionmentioning
confidence: 99%
“…2 Malignant transformation is characterized by a more rapid and consistent progression. Individual growth rates of melanoma are variable and dependent on specific tumor characteristics, but studies have shown an average growth of 0.96 to 1.8 mm/year in LBD 3,4 and 1.12 mm/ year in thickness. 3 Treatment within a few weeks is recommended because growth over such a short period is not believed to be sufficient to require radiation dose alteration while not increasing the risk of metastasis significantly.…”
mentioning
confidence: 99%